Effects of hydrated lime on radionuclides stabilization of Hanford tank residual waste. (October 2017) - Wang, Guohui; Um, Wooyong; Cantrell, Kirk J.; Snyder, Michelle M.V.; Bowden, Mark E.; Triplett, Mark B.; Buck, Edgar C.
Abstract: Chemical stabilization of tank residual waste is part of a Hanford Site tank closure strategy to reduce overall risk levels to human health and the environment. In this study, a set of column leaching experiments using tank C-104 residual waste were conducted to evaluate the leachability of uranium (U) and technetium (Tc) where grout and hydrated lime were applied as chemical stabilizing agents. The experiments were designed to simulate future scenarios where meteoric water infiltrates through the vadose zones into the interior of the tank filled with layers of grout or hydrated lime, and then contacts the residual waste. Effluent concentrations of U and Tc were monitored and compared among three different packing columns (waste only, waste + grout, and waste + grout + hydrated lime). Geochemical modeling of the effluent compositions was conducted to determine saturation indices of uranium solid phases that could control the solubility of uranium. The results indicate that addition of hydrated lime strongly stabilized the uranium through transforming uranium to a highly insoluble calcium uranate (CaUO4 ) or similar phase, whereas no significant stabilization effect of grout or hydrated lime was observed on Tc leachability. The result implies that hydrated lime could be a great candidate for stabilizing Hanford tank residual wastes where uranium is one of the main concerns. Highlights: Hanford tank residual waste could be stabilized by grout. Addition of hydrated lime stabilized uranium from leaching through CaUO4 . XRD, SEM/EDS and thermodynamic model revealed uranium mineral transformation.